Diálogos e práxis no processo de formação humana no âmbito do Proeja no Ifes - Zen, Eliesér Toretta (2016)
This research had a philosophical praxis analysis between students and professors as main goal, and took place in a campus of a federal institute named Instituto Federal do Espírito Santo, state in which it is located. The thesis was based in a critic dialog in this Labor Safety class as a philosophic attitude that integrates the technical and humanistic dimensions of human formation at Proeja. The thesis defends that the philosophic praxis in the class is evidenced as a integrating element between different curricular components by practicing the critic dialog in capitalist social relationships and its applications in transforming the social and personal reality. The investigation was guided by the following issue: which has been the praxis in a Labor Safety class and which are the possibilities of being settled as space and time of human formation development of students and professors at Proeja? The theoretical methodological contribution has its base in the historical-dialectical materialism, and it is based in the philosophy of praxis between Marx, Gramsci and Freire's dialogs. As a qualitative research, a methodological approach to participatory research that is carried out based on belonging to the community, participation and dialogue between researchers, students and teachers during classes and interviews. The participating individuals were 12 students and seven professors of a Labor Safety class of Proeja, in which we were acting with the observation in the periods of 2014/2 and 2015/1; there were yet two Proeja alumni students, totalizing 14 students and seven participating professors. The results reveal that through the philosophical praxis students and professors exercised the critic dialog among inequalities caused by the capitalist system by problematizing unemployment, outsourcing, land concentration and the media monopoly. Thus, the dialogues between students and teachers signaled for a philosophical praxis that aims at the transformation of capitalist social relations in view of integral human formation in Proeja.